INTEGRATION OF DEEP LEARNING AS AN EDUCATIONAL INNOVATION STRATEGY FOR ISLAMIC BOARDING SCHOOLS (PESANTREN) IN THE DIGITAL ERA - Muzakir, Muchammad Ibnu; Akhirudin, Muhammad Towil; Idham, Idham; Samiyono, Samiyono (Jurnal As-Salam, 2025)
This study explores the integration of the pedagogical Deep Learning (DL) approach, specifically the Meaningful, Mindful, and Joyful (MMJ) framework, within the traditional educational system of Indonesian pesantren. The aim is to analyze the compatibility, challenges, and operationalization of DL to enhance learning outcomes and prepare students for the demands of the digital era. A qualitative case study approach was employed at pesantren Darunnajah in Bogor, involving in-depth interviews with 12 participants (3 teachers, 6 students, and 3 administrators), observations, and document analysis. The findings highlight a strong theoretical alignment between DL and pesantren's core educational values, such as Fahm (deep comprehension), Ijtihad (critical reasoning), and Adab (moral development). Empirically, teachers reported improved student engagement and reflective learning practices, with one educator noting, "The MMJ framework helps students connect religious lessons to their daily lives, making learning more relevant." However, the study identifies key challenges, including infrastructure gaps, diverse levels of digital literacy, and the need to balance digital innovation with the preservation of moral guidance. Strategies such as blended learning models and focused teacher training are recommended. The integration of DL within pesantren represents a strategic pedagogical evolution, empowering students to develop both religious and modern competencies. Future research should focus on the longitudinal impacts of DL on student outcomes.